2016
DOI: 10.2967/jnumed.116.178749
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Distant Metastases on 18F-FDG PET/CT at Initial Staging of Breast Cancer: Comparison of Women Younger and Older Than 40 Years

Abstract: Women who have breast cancer and are younger than 40 y have a poorer outcome than older women. A higher rate of undetected metastases at the time of diagnosis in younger women has been proposed to account for this difference. Our main objective was to test this hypothesis by comparing the distant metastasis rate (DMR) on initial 18 F-FDG PET/CT in a group of breast cancer patients younger than 40 y (,40 y group) with that in a group of breast cancer patients older than 40 y ($40 y group). An assessment of asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…13 Other authors have published similar results. 26,27 The rate of pulmonary nodule detection in this study was 27.7%, which is higher than that reported in the radiation oncology literature, but consistent with other large-volume studies. 28,29 The high detection rate of incidental pulmonary nodules has led to recommendations for additional follow-up from the Fleischner Society and the American College of Chest Physicians.…”
Section: Discussionsupporting
confidence: 88%
“…13 Other authors have published similar results. 26,27 The rate of pulmonary nodule detection in this study was 27.7%, which is higher than that reported in the radiation oncology literature, but consistent with other large-volume studies. 28,29 The high detection rate of incidental pulmonary nodules has led to recommendations for additional follow-up from the Fleischner Society and the American College of Chest Physicians.…”
Section: Discussionsupporting
confidence: 88%
“…Age: Two studies reported the influence of age on DM rate[27,33]. In the first study, among 134 young patients (< 40-year-old), the DM rate was 5% and 10.9% for clinical stage I and stage II, respectively[27].…”
Section: Resultsmentioning
confidence: 99%
“…In the first study, among 134 young patients (< 40-year-old), the DM rate was 5% and 10.9% for clinical stage I and stage II, respectively[27]. In the second study, among 214 stage I-III patients, the DM rates did not differ significantly between the age groups of < 40-year-old and ≥ 40-year-old[33]. However, the DM rates in the younger age group were 8% in stage I, 9% in stage IIA and 17% in stage IIB, equating to 2x’s higher than those found in the first study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield of PET/CT in younger patients was not compared with the yield in older patients [12]. In a study from the Institut Curie in Paris, no significant difference in the distant metastasis rate was observed between the <40 years group and the ≥40 years group (107 patients in each group; distant metastases rate: 21% and 22%, respectively; P = 1) [13].…”
mentioning
confidence: 99%